2022
DOI: 10.3897/neobiota.76.82964
|View full text |Cite
|
Sign up to set email alerts
|

Changing climate may mitigate the invasiveness risk of non-native salmonids in the Danube and Adriatic basins of the Balkan Peninsula (south-eastern Europe)

Abstract: Salmonids are an extensively hatchery-reared group of fishes that have been introduced worldwide mainly for their high commercial and recreational value. The Balkan Peninsula (south-eastern Europe) is characterised by an outstanding salmonid diversity that has become threatened by the introduction of non-native salmonids whose potential risk of invasiveness in the region remains unknown and especially so under predicted climate change conditions. In this study, 13 extant and four horizon non-native salmonid sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…In addition to the genetic analyses, the invasive character of the AT lineage has been highlighted in recent research, which showed the rapid adaptation of this lineage to the different conditions in natural watercourses, the consumption of a wide range of available food and competition for food and space, as well as diet overlap with native DA lineage individuals (Piria et al, 2020). Also, in assessment of invasiveness risk in the Danube and Adriatic basins across four Balkan countries, out of 13 existing and four horizon non-native salmonid species, S. trutta of the AT lineage showed a very high risk of invasiveness in the current climate conditions (Marić et al, 2022). In addition to At1, the non-native Da2 haplotype has also a significant impact on disrupting the genetic structure of the native Croatian populations of brown trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the genetic analyses, the invasive character of the AT lineage has been highlighted in recent research, which showed the rapid adaptation of this lineage to the different conditions in natural watercourses, the consumption of a wide range of available food and competition for food and space, as well as diet overlap with native DA lineage individuals (Piria et al, 2020). Also, in assessment of invasiveness risk in the Danube and Adriatic basins across four Balkan countries, out of 13 existing and four horizon non-native salmonid species, S. trutta of the AT lineage showed a very high risk of invasiveness in the current climate conditions (Marić et al, 2022). In addition to At1, the non-native Da2 haplotype has also a significant impact on disrupting the genetic structure of the native Croatian populations of brown trout.…”
Section: Discussionmentioning
confidence: 99%
“…In Croatian fish farms, brown trout of the AT lineage are mainly bred, so consequently the rivers are most likely stocked with these individuals due to their availability (Marić et al, 2022). In this way, non-native genetic material enters natural watercourses (Piria et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Huchen occurs also in the upper reaches of the River Ibar and has been released in the rivers Moravica and Đetinja, which are tributaries of the River Zapadna Morava (Hegediš et al, 2005). In addition, huchen was introduced into the rivers Jerma and Nišava (the Južna Morava catchment area) and into the River Mlava, which flows directly into the Danube (Marić et al, 2022). This article reports the first finding of huchen in the River Grza, outside its already-known range in Serbia.…”
Section: Introductionmentioning
confidence: 96%